Public Receptivity Towards LGBT in Recent Times Malaysia: LGBT Perspectives - Collin, Jerome; Ting, Su Hie; Yuwana, Podin; Sharifah Sophia, Wan Ahmad (HRMARS, 2021)
The increasing visibility of LGBT communities has generated considerable public debate in Malaysia and many research studies have examined (and are currently examining) the subject matter. This article presents the findings of a qualitative study that aims to examine public receptivity towards LGBT in present-day Malaysia. Views from 15 LGBT individuals from Malaysia who consented to participate in the study were gathered via interviews and analyzed using Creswell’s (2014) qualitative data analysis procedures. The findings show that the participants viewed public receptivity towards LGBT in Malaysia from two perspectives, despite their varying views on the subject matter based on their personal experiences: 1) religion and the cultural norms about gender and sexuality that are regulated within the ethnic groups the participants belong to continue to influence public receptivity towards LGBT; and 2) certain segments of the Malaysian public are showing receptivity towards LGBT in Malaysia as can be seen in the emergence of LGBT figures on social media, and their legions of followers who recognize and accept their non-normative gender or sexual identity. The findings have implications for current and future studies that examine the changing realities of Malaysia’s LGBT communities in recent times.